Effect of sodium carboxymethylcelluloses on the disintegration, dissolution and bioavailability of lorazepam from tablets - Singh J. (My University, 2025)
A new range of soudium carboxymethylcelluloses (i.e. nymcelR types ZSB-10, ZSB-16 and ZSD-16) were included into lorazepam tablet formulations to improve the disintegration, dissolution and bioavailabiltiy of the drug. Tablets of the batch G containing 5% Nymcel ZSB-16 exhbibited quicker disintegration, faster dissolution, and higher rate and extent of bioavailability in mongrel dog in comparison to tablets of the other batches. © 1992 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.